Constructing the Children Chorus Guidebook for Teaching Student at Jinhua Primary School in Zhengzhou, Henan Province - Baolin, Zhang; Yodwised, Chutasiri (Asia Pacific Journal of Religions and Cultures, 2024)
The objectives of this study are four folds:(1) To study the teaching method of children’s chorus. (2) To construct a children’s chorus teaching guidebook (3) To use a children’s chorus guidebook in Jinhua Primary School. (4) To evaluate the result of teaching by using the guidebook. The research method is a mixture of qualitative and quantitative methods. Qualitative research is the analysis and research of the children’s chorus method, and quantitative research is the teaching of the experimental group. The population is 50 students in Grade 5 of Jinhua Primary School. The findings of this paper are as follows :(1) I studied books and articles related to children’s chorus, learned training methods, vocalization, resonance, music theory solfeggio and emotional processing from children’s chorus experts, and consulted relevant information about each song, singing skills, and music analysis. (2) The Children’s Chorus Guide consists of vocal skills, resonance, intonation, rhythm, solfeggio ear training, pronunciation, processing and expression, stage performance skills, history and development, processing and expression of aesthetic characteristics, and Chinese and foreign children’s chorus repertoire. (3) The lesson plan consists of 16 lessons followed by predictive, formative, and summative tests. (4) The effectiveness of using the guide to teach, and the students’ learning outcomes are at a good level; This guide is suitable for high-level teaching.